HUBUNGAN STATUS GIZI, RIWAYAT KELUARGA, USIA MENSTRUASI DAN LAMA MENSTRUASI DENGAN KEJADIAN NYERI MENSTRUASI PADA SISWI SMAN 2 ACEH BARAT - Marsela, Lara; Rinawati; Khairunnas; Wahyu Muhsin, Sri (Universitas Cokroaminoto Palopo, 2025)
A number of factors, including nutritional status, family history, menstrual age, and duration of menstruation, can contribute to menstrual pain, which is characterized by lower abdominal or back pain that occurs before or during the menstrual cycle. Menstrual pain can also cause anxiety and discomfort. The purpose of this research is to ascertain the association between the occurrence of menstrual discomfort in female students at SMAN 2 Aceh Barat and their nutritional state, family history, menstrual age, and monthly length. With a cross-sectional design and a quantitative analytical research methodology, the Lemeshow formula yielded a sample size of 156 individuals. A questionnaire including questions about family history, early menstrual age, monthly length, and numerical rating scale (NRS) assessment is the tool used. The Chi-Square test is the analysis that is used. The findings indicated that, among female students at SMAN 2 Aceh Barat, there was no significant correlation between the occurrence of menstrual discomfort and nutritional status (p-value = 0.814> 0.05). The occurrence of menstruation discomfort among female students at SMAN 2 Aceh Barat was significantly correlated with family history (p-value = 0.003<0.05). The occurrence of menstrual discomfort among female students at SMAN 2 Aceh Barat was significantly correlated with menstrual age (p-value = 0.000<0.05). A p-value of 0.000<0.05 indicated a correlation between the length of menstruation and the prevalence of menstrual discomfort among female students at SMAN 2 Aceh Barat. According to the researcher, teenage females should become more knowledgeable and conscious of reproductive health, particularly as it relates to monthly discomfort. Teenagers who go through menstruation and have a family history of menstrual discomfort should be especially watchful and take preventative action early on. This includes controlling stress, maintaining a healthy lifestyle, exercising often, and using painkillers when needed.